PERCERAIAN AKIBAT HUTANG PIUTANG ISTRI TANPA SEPENGETAHUAN SUAMI PERSPEKTIF IMAM SYAFI’I : Studi di Desa Karangnongko Poncokusumo Malang - Ulum, Bahrul; Yusqi, Muhammad (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2025)
This study examines how debts incurred by a wife without her husband's knowledge affect marital harmo ny and how such actions may serve as valid grounds for divorce. Divorce is a complex social phenomenon influenced by various factors, and financial secrecy is one of the key triggers of marital conflict. When a wife secretly takes on debt, it can create distrust, emotional strain, and significant financial pressure that disrupt the stability of the household. Using field research methods—including interviews, observations, and document analysis—this study interprets the findings through established theories to understand the psychological and emotional consequences of such actions and their impact on divorce decisions. The results show that, according to Imam al-Shafi‘i, a wife who incurs debt without informing her husband undermines family well-being and violates the principles of trust and shared responsibility in marriage, highlighting the importance of financial transparency and open communication in maintaining marital harmony